2009
DOI: 10.1016/j.ijid.2008.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of common opportunistic infections in HIV-infected individuals in Pune, India: analysis by stages of immunosuppression represented by CD4 counts

Abstract: The high incidence of commonly reported OIs in Indian HIV-infected individuals highlights the need for early screening and also the need to increase awareness in healthcare providers, in order to improve decisions regarding prophylaxis for prevention and appropriate therapeutic intervention. Emphasis needs to be given to the early diagnosis and management of tuberculosis in HIV-infected individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
78
5
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 30 publications
14
78
5
3
Order By: Relevance
“…Most common presenting complaint of patients in this study was Fever = 30% Present study showed opportunistic infections in 48.3 % of total cases and most common was pulmonary tuberculosis (24/60 = 40%).Manish Ghete et al 13 reported incidence of Opportunistic infection to be 35.7/100 person years and the most common infection in his study was Tuberculosis. Tuberculosis and oral candidiasis are the most commonly reported HIV-related Opportunistic infections in India.…”
Section: Discussionsupporting
confidence: 45%
“…Most common presenting complaint of patients in this study was Fever = 30% Present study showed opportunistic infections in 48.3 % of total cases and most common was pulmonary tuberculosis (24/60 = 40%).Manish Ghete et al 13 reported incidence of Opportunistic infection to be 35.7/100 person years and the most common infection in his study was Tuberculosis. Tuberculosis and oral candidiasis are the most commonly reported HIV-related Opportunistic infections in India.…”
Section: Discussionsupporting
confidence: 45%
“…15 In another study, Saurabh et al found the same order of incidence with TB at the top of all the OI's.…”
Section: Discussionmentioning
confidence: 85%
“…Opportunistic infections (OIs) are important co-morbidities in PLWHAs 18 and they influence the morbidity and mortality due to HIV infections. This study showed that in seven of the patients without bacteriuria and four patients with bacteriuria, there was growth of candida in the urine.…”
Section: Discussionmentioning
confidence: 99%